2011
DOI: 10.1111/j.2041-1014.2011.00607.x
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus mutans strains recovered from caries‐active or caries‐free individuals differ in sensitivity to host antimicrobial peptides

Abstract: SUMMARY Antimicrobial peptides (AMPs) are among the repertoire of host innate immune defenses. In the oral cavity, several AMPs are present in saliva and have antimicrobial activities against oral bacteria, including Streptococcus mutans, a primary etiologic agent of dental caries. In this study, we hypothesized that unique S. mutans strains as determined by DNA fingerprinting from sixty 13 year-old subjects with or without caries experience would have different susceptibilities to α-defensins-1-3 (HNP-1-3), β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
52
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 58 publications
3
52
0
5
Order By: Relevance
“…Except for hBD-1, all peptides demonstrated nearly 100% bactericidal activity with concentrations less than 10 mg/l. Some authors have suggested that the reduced concentration of certain peptides could be associated with dental caries in children (Tao et al, 2005;Davidopoulou, Diza, Menexes, & Kalfas, 2012;Phattarataratip et al, 2011). The levels of a-defensin (hNP1-3) (Tao et al, 2005) and LL-37 (Davidopoulou et al, 2012) were lower in saliva from caries-active children compared to caries-free children.…”
Section: Introductionmentioning
confidence: 99%
“…Except for hBD-1, all peptides demonstrated nearly 100% bactericidal activity with concentrations less than 10 mg/l. Some authors have suggested that the reduced concentration of certain peptides could be associated with dental caries in children (Tao et al, 2005;Davidopoulou, Diza, Menexes, & Kalfas, 2012;Phattarataratip et al, 2011). The levels of a-defensin (hNP1-3) (Tao et al, 2005) and LL-37 (Davidopoulou et al, 2012) were lower in saliva from caries-active children compared to caries-free children.…”
Section: Introductionmentioning
confidence: 99%
“…LL‐37 has been demonstrated in human whole saliva from both adults and children , and can also be found in saliva isolated from human parotid and submandibular/sublingual glands, showing that hCAP18/LL‐37 is indeed produced by cells of the major salivary glands . It has been reported that LL‐37 possesses antibacterial effects against many strains of oral bacteria, including Streptococcus mutans and Porphyromonas gingivalis which are associated with caries and periodontitis . Patients with the congenital disease Kostmann's syndrome, characterized by neutropenia and frequent and severe infections, have either no or extremely low levels of LL‐37 in plasma and saliva .…”
mentioning
confidence: 99%
“…Interestingly, LL‐37 shows antimicrobial activity against many oral bacteria, such as Porphyromonas gingivalis , Streptococcus mutans , Treponema denticola , Fusobacterium nucleatum , and Prevotella intermedia . With respect to S. mutans , LL‐37 seems to have a more pronounced cytotoxic effect on S. mutans strains isolated from caries‐free individuals than on S. mutans strains isolated from caries‐active individuals, suggesting that S. mutans strains recovered from caries‐active subjects have become less sensitive to LL‐37‐evoked cytotoxicity .…”
mentioning
confidence: 99%